Morphoagronomic variability in specimens of wild papaya (Carica cubensis Solms) in Cuba - Rodríguez-Cabello, Jesús (2022)
Introduction. Papaya is the third most important tropical fruit worldwide. However, in the wild variety, endemic to Cuba, there is no evidence of studies for its conservation, cultivation or breeding programs. Objective. To evaluate wild papaya specimens from the Almendares-Vento basin, with the use of morphoagronomic descriptors, to contribute to the conservation and value its productive potential and characters of interest for the genetic improvement of C. papaya. Materials and methods. The research was developed between 2008 and 2018, in situ in the Almendares-Vento Basin, Mayambeque, and traditional growing conditions, at the Instituto Nacional de Ciencias Agricolas, San Jose of Las Lajas, Cuba. The evaluations were carried out using sixteen morphoagronomic descriptors recommended for the species. In 2016, seeds from eleven plants were collected for individual ex situ evaluation. The qualitative descriptors were described using photographic images and for the quantitative descriptors in situ, descriptive statistics were calculated for each of the variables evaluated. For the ex situ evaluations, a principal component analysis and a biplot were performed. For each descriptor, 95 % confidence intervals were calculated. Results. In situ, the wild papaya population was made up of specimens that lived isolated and distant from each other. Under traditional cultivation conditions, they showed morphoagronomic variability in the number of fruits and their dimensions, °Brix and acidity. In addition to their ecological value, the aforementioned characters revealed potential qualities in the identification of promising genotypes, related to the market and use in crop improvement. Conclusion. The fruits showed physical and bromatological properties that make wild papaya a promising phytogenetic resource for use in crop improvement and as a production alternative for production under traditional growing conditions.